1999
DOI: 10.1038/sj.bmt.1701531
|View full text |Cite
|
Sign up to set email alerts
|

Increases in 4-hydroxynonenal and hexanal in bone marrow of rats subjected to total body X-ray irradiation: association with antioxidant vitamins

Abstract: Summary:Radiation-induced lipid peroxidation and its association with antioxidant vitamins in the bone marrow (BM), of rats subjected to total body irradiation (TBI) of X-rays at a dose of 3 Gy was investigated. The concentration of vitamin C in the BM decreased at 4 h, and reached about 2% of the control level at 24 h after irradiation. The concentration of vitamin E in the BM also decreased to 43% at 24 h. Corresponding to the decrease in vitamin E concentration, the concentration of 4-hydroxynonenal (HNE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Because of their ultra-short half time they are more difficult to detect in whole blood, homogenates, or breath [19,20]. Volatile aldehydes have been studied as specific markers of LPO in asthma/chronic obstructive pulmonary disease [21], ARDS [22], in bone marrow after total body X-ray irradiation [23], in diabetes mellitus [24], and diabetic nephropathy [25], malnutrition [26], atherosclerosis [27], stroke patients [13], and most recently in brain tumors [28]. However, no comparative study has been performed yet for different LPO-marker pattern between various organ failures including these volatile aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their ultra-short half time they are more difficult to detect in whole blood, homogenates, or breath [19,20]. Volatile aldehydes have been studied as specific markers of LPO in asthma/chronic obstructive pulmonary disease [21], ARDS [22], in bone marrow after total body X-ray irradiation [23], in diabetes mellitus [24], and diabetic nephropathy [25], malnutrition [26], atherosclerosis [27], stroke patients [13], and most recently in brain tumors [28]. However, no comparative study has been performed yet for different LPO-marker pattern between various organ failures including these volatile aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the bone marrow of mice is depleted of endogenous vitamins C and E after TBI at doses as low as 50 cGy within 24 h (18). Depletion of vitamins C and E coincided with increased markers of oxidative cellular damage in the bone marrow (18,19). Irradiation with 3 Gy resulted in repletion of endogenous vitamin C and E levels in the bone marrow 1 week after exposure; however, no recovery was observed after 6 Gy TBI (18).…”
Section: Introductionmentioning
confidence: 99%
“…[6] We also reported that feeding rats and mice a diet containing insufficient or excess VE did not modify TBI-induced chromosomal damage or lipid peroxidation in the bone marrow. [4,7] In contrast, Przbyszewski et al [8] reported that VE treatment prevents the increase in lipid peroxide in the serum and heart of rats given gamma-irradiation.…”
Section: Introductionmentioning
confidence: 91%
“…[3,4] However, the changes were delayed for several days in the plasma compared to the bone marrow. [4] Similar delayed onset of lipid peroxidation in the liver and spleen has also been reported by other investigators. [5] Breath ethane, a marker of n-3 fatty acid oxidation, has been shown to increase on day 2 after TBI in humans.…”
Section: Introductionmentioning
confidence: 97%